Effects of Larval Density and Habitat Drying on Developmental Success of Ochlerotatus albifasciatus (Diptera: Culicidae) in Urban Rain Pools: Evidence From Field and Experimental Studies - Fischer, Sylvia Cristina (2014)
Ochlerotatus albifasciatus (Macquart) (Diptera: Culicidae) larvae develop synchronously after rainfall events in ephemeral or temporary pools, where they occasionally attain very high abundance. The aims of the current study were to analyze the response of life history parameters such as daily larval mortality, time to pupation, and adult size of Oc. albifasciatus to increasing larval density under controlled conditions, and to analyze the relationships of daily larval mortality with density and environmental variables (drying rate, temperature, and season) in urban rain pools in Buenos Aires, Argentina. An exponential increase in mortality was observed at high larval densities under controlled conditions. Development times and adult size (wing length) differed between males and females, and were also affected by density. Development times extended for 0.36 d for each order of magnitude of increase in larval density, and wing length decreased 0.0021 mm per additional larva in 600 cm2. Larval density in the field varied from <1 larva per square meter to nearly 1100 larvae per square meter. Daily larval mortality values in the field were variable (0.02–0.91), positively related to the drying rate, and exhibited seasonal differences. No significant relation with larval density or temperature was found in the field. It remains to be established whether the density-independent mortality observed in this study is a generalized pattern of Oc. albifasciatus populations in Buenos Aires Province or a pattern restricted only to urban habitats.